TỔNG HỢP VẬT LIỆU NANO PHÁT QUANG YVO4:Eu3+ VÀ YVO4:Er3+ BẰNG PHƯƠNG PHÁP PHẢN ỨNG NỔ - Vũ, Nguyễn; Văn, Nguyễn Đức; Lộc, Đinh Xuân; Mạnh, Đỗ Hùng; Roãn, Phạm Đức (Vietnam Journal of Chemistry, 2012)
YVO4:Eu3+ and YVO4:Er3+ nanophosphors were prepared via combustion synthesis using urea as fuel and metal nitrates as precursor. Characterization of prepared materials was investigated by thermogravimetric and differential thermal analysis, infrared spectra, X-ray diffraction, scanning electron microscopy and photoluminescent spectra. The photoluminescent spectra of YVO4:Eu3+ are described by the well-known 5D0-7FJ transition (J = 1, 2, 3, 4) of Eu3+ ions with the strongest emission in the red region for J = 2. YVO4:Er3+ shows green emission coresponding to the 2H11/2 - 4I15/2 and 4S11/2 - 4I15/2 transitions of Er3+ ion. The effects of synthesis conditions on structure and optical properties have been investigated.